WHALE SHARK RHINEODON TYPUS SMITH LANDED AT KARWAR, KARNATAKA - Pai, M V; Nandakumar, G; Telang, K Y (Indian Journal of Fisheries, 2011)
A female whale shark, Rhineodon typus Smith, measuring 8.81 m intotal length was landed at Karwar in the third week of January 1981 [reportedas measuring 3.81 m in length (Anon 1981)]. This is the first record of such anoccurrence in North Kanara District. The earliest record of a whale shark alongthe Karnataka coast was made by Kaikini et al (1959) at Suratkal in SouthKanara District